Molecular Typing of Uropathogenic Escherichia coli Strains Isolated from Patients by Random Amplified Polymorphic DNA-PCR (RAPD-PCR) - Faraji, Zeynab; Khasheii, Behnoush; Ghaemi, Ezzat Allah; Anvari, Shaghayegh; Rajabnia, Ramezan; Jamali, Ailar (Archives of Medical Laboratory Sciences, 2021)
Background and Aim: Urinary tract infections (UTIs) are one of the most common pathological diseases in communities and hospitals, often caused by uropathogenic Escherichia coli (UPEC). The use of microbial strains typing is an integral part of epidemiological surveys of infectious diseases to identify epidemics, detect the infection source, track and recognize pathogenic strains. In this study, uropathogenic Escherichia coli (UPEC) strains isolated from patients living in Gorgan were typed using RAPD-PCR. Methods: In total, 187 Escherichia coli strains isolated from urine samples of inpatients and outpatients of Gorgan city from 2010 to 2016 were analyzed by the RAPD-PCR method using two primers. Using GelClust and FigTree software, the respective dendrograms were plotted by unweighted pair group method with arithmetic mean (UPGMA). Results: In our research, 614 bands were detected using two primers. The highest frequency of bands was obtained in 400 bp and 500 bp with 65 repeats and the lowest number of bands was in 2500 bp and 3000 bp with one repeat and 32 clusters. The largest number of isolates (i.e.14) was placed in cluster 16. Most bands were polymorphic, indicating high genetic diversity in isolates. Conclusion: Analysis of 32 clusters of our study by the RAPD-PCR method showed that the studied clusters do not have a specific and unique feature and the scattering of isolates properties are equal among the clusters. Because each cluster had its characteristics, E. coli strains in the region have great genetic diversity. *Corresponding Author: Ailar Jamali; Email: jamali@goums.ac.ir; ORCID: https://orcid.org/0000-0002-4612-8144 Please cite this article as: Faraji Z, Khasheii B, Ghaemi EA, Anvari S, Rajabnia R, Jamali A. Molecular Typing of Uropathogenic Escherichia coli Strains Isolated from Patients in Gorgan by Random Amplified Polymorphic DNA-PCR (RAPD-PCR). Arch Med Lab Sci. 2021;7:1-7 (e17). https://doi.org/10.22037/amls.v7.34383